Access to the Internet and the Chinese household consumption structure: Based on IV regression and PSM analysis. (September 2020) - Wang, Liping; Deng, Hao
Abstract: Based on the data of China's Household Finance Survey (CHFS) in 2017 consisting of 38230 samples across China, this paper uses the instrument variable (IV) regression method and the propensity score matching (PSM) technique to study the influence of access to the Internet on the household consumption structure. The conclusions are as follows: first, access to the Internet is conducive to the upgrading of the consumption structure of the residents. Increase of the income, assets and education level could upgrade the consumption structure. Second, people who do not use the Internet will upgrade the consumption structure if they use the Internet, but the upgrading degree of the consumption structure is limited by the income level. Third, from the regional perspective, the Internet can promote the upgrading of consumption structure in the eastern and western regions of China, but it has no significant effect on the consumption structure in the central and northeast regions.